PERAN KEPEMIMPINAN VISIONER KEPALA SEKOLAH SEBAGAI FAKTOR PENENTU KEBERHASILAN MBS DI SD NEGERI 4 PANJER - Anak Agung Gede Agung; Chindytia; Komang Emaliana Trianita; Hermayanti, Ni Kadek Diah; Ni Komang Sri Devikananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) and describe the role of the principal’s visionary leadership in supporting the success of SBM at SD Negeri 4 Panjer. This research employed a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews and direct observations involving the school principal as the main research subject. The findings revealed that the implementation of SBM at SD Negeri 4 Panjer has been carried out effectively through participatory, transparent, and accountable school management involving teachers, education staff, parents, school committees, and other stakeholders. The principal demonstrated visionary leadership by encouraging innovation in learning, strengthening collaboration among school members, and supporting the implementation of the Merdeka Curriculum. The study also found that teamwork, open communication, and stakeholder participation became supporting factors in the success of SBM implementation. Meanwhile, several obstacles were identified, such as limited budget, inadequate technology-based facilities, and differences in stakeholders’ understanding of SBM. Overall, the visionary leadership of the principal plays a strategic role in creating an adaptive, collaborative, and quality-oriented school management system